Forty Years of Modern Art 1945-1985. (London : Tate Gallery, 1986)
Gorky, Arshile ; Pollock, Jackson ; de Kooning, Willem ; Newman, Barnett ; Hofmann, Hans ; Francis, Sam ; Butler, Reg ; Moore, Henry ; Hartung, Hans ; Jorn, Asger ; Rothko, Mark ; Dubuffet, Jean ; Nicholson, Ben ; Pasmore, Victor ; Vasarely, Victor ; Albers, Josef ; Arman ; Bacon, Francis ; etc.
Forty Years of Modern Art 1945-1985, The Tate Gallery, London, 19 February - 27 april 1986
boek